Lost Of The Emotional Side Of Kathy In Romanek's Never Let Me Go Movie (2010): A Psychoanalytic Approach - Jantini, Ririn Tri; , Drs. Abdillah Nugroho, M. Hum; , Drs. Sigit Haryanto, M.Hum (2014)
The researcher analysis the lost of the emotional side of Kathy in Romanek's Never Let Me Go movie (2010) by a psychoanalytic approach. The researcher sets two objectives: the first is to analyze the movie based on its structural elements, and the second is to analyze the lost of the emotional side of Kathy based on the psychoanalytic approach. This study is a qualitative using the movie of Never Let Me Go as the object analysis. There are two kinds of data sources: primary and secondary. The primary is Never Let Me Go movie, director by Romanek, and the secondary consists of the other data such as biography of the author, and books of the literary especially psychological book. Technique of the data collecting is documentation the step are: watching the movie, reading the movie script, determining the character that be analyzed, taking notes of important parts in both primary and secondary data , cclassifying and determining the relevant data, and taking notes from the material and some other resources related to the movie. In analyzing the data, the researcher employs descriptive qualitative analysis. The outcome of the study is as follows: first, structural analysis: Never Let Me Go is a 2010 British dystopian drama film based on Kazuo Ishiguro's 2005 novel of the same name. The film was directed by Mark Romanek from a screenplay by Alex Garland. Theme in the film is "the strength to put up with temporary life". This is possible because Kathy has a good heart, succumb in every respect and strength to survive. Secondly, based on the psychoanalytic analysis: in this movie, the researcher found that the main character has a psychological condition that is not good. This is evidenced by the injustices in life. Although she knew that she was the same with other people, there's nothing different with those who help her and she will die for other people's lives. But she will still do its donors despite desire but it is not her fate as a child born to at donated her limbs. Kathy is faced with conflict between id, ego, and superego affecting her life. Finally the superego dominated her ego from then id.